Implementation of CSMA/CA-Based MAC Protocol for Optical Camera Communication - Muhammad Miftah Faridh; Herfandi Herfandi; Ones Sanjerico Sitanggang; Muhammad Rangga Aziz Nasution; Huy Nguyen; Yeong Min Jang (IEEE Access)
Optical camera communication (OCC), a branch of optical wireless communication (OWC), enables data transmission using LEDs and reception via cameras. This technology offers benefits such as a broad spectrum, low cost, high efficiency, and resistance to electromagnetic interference. However, OCC faces challenges in medium access management, which necessitates the development of effective medium access control (MAC) protocols. The IEEE 802.15.7 standard proposes MAC protocols tailored for various OCC modes and simplifies frame structures. In this study, we develop and test a MAC protocol based on carrier sense multiple access with collision avoidance (CSMA/CA) and integrate a novel transform alignment technique aimed at optimizing the bit error rate (BER) performance. By addressing the inherent medium access challenges in OCC, such as signal interference and access contention, the new protocol significantly boosts data transmission efficiency and enhances communication reliability.